Certification Test in Evaluation of The Implementation of Competencythe Profession Certification Institution (LSP) UPN “Veteran” Jawa Timur - Gideon Setyo Budiwitjaksono; Endang Iryanti (Nusantara Science and Technology Proceedings, 2020)
The aim of this research is to evaluate the implementation of the competency certification test at LSP UPN Veteran East Java to improve human resources who are able to provide and produce competitive graduates, as well as provide recommendations in maintaining and developing new competency schemes in each study program. This study uses a quantitative descriptive method using a survey through a questionnaire instrument designed with the jotform application and sent to respondents via email. Determination of the sample using a minimum sample based on the Slovin formula, with respondents who have taken the competency certification test held by LSP UPN Veteran East Java. Data analysis used the CIPP model with components; context, input, process, product related to the evaluation of the implementation of the competency scheme certification test. The results show that; First, the implementation of the competency certification test is based on the stated vision and mission of the higher education. Competency certification is an important attribute because it is based on three components of competency dimensions, namely knowledge, skills and attitudes that must be possessed by a person. Second, the implementation of the competency certification test involves Competency Assessors (Askom) who have received adequate basic training and already have Competency Assessor certification from BNSP. Third, the implementation of the competency certification test at LSP UPN Veteran East Java has been following the plan, taking into account several stages starting from socialization, communication, implementation, and evaluation, with various interested parties. Fourth, the implementation of the competency certification test is a series of learning processes carried out by students according to the competency scheme established based on the Standard Kualifikasi Kerja Nasional Indonesia (SKKNI) in achieving learning objectives in Higher Education.